PENGARUH IMPLEMENTASI BIMBINGAN SOSIAL TERHADAP PERILAKU DISIPLIN ANAK BINAAN PANTI ASUHAN YAYASAN PEMBANGUNAN DIDIKAN ISLAM - Maya Nurhaliza; Fauzi Kurniawan; Mahfuzi Irwan (Journal Education for All : Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2020)
This research was motivated by the need for guidance in improving the discipline of the orphanage assisted children, seen from their daily lives when researchers made initial observations. Of the total there are 60% of the orphaned children who need to be given guidance in improving discipline in the orphanage. The purpose of this study was to determine the effect of the implementation of social guidance on the disciplinary behavior of the assisted children in Islamic education development foundations. This type of research is a quasi-experimental, by taking the subject through purposive sampling technique, namely 23 children assisted by the orphanage. Data collection techniques were carried out through observation and questionnaires. The results showed that the overall average score before treatment (experiment) was in the relatively low criteria, namely 1.72% with the highest score of 63 and the lowest score of 48. While the overall average score after treatment was in the high category, namely 3.19% with the highest score of 108 and the lowest score of 91, so that the level of discipline of the orphanage assisted children obtained a significant difference. Based on these results, the hypothesis states that social guidance has an effect on the level of discipline, namely tcount> ttable 199.56> 1.720. Thus it can be concluded that social guidance has an effect on increasing the disciplinary behavior of the children assisted by the Islamic education development foundations.